A High‐Nuclear Isopolymolybdate Cluster Assembled with an Anionic [Mo24O48(OMe)32]8− and Two Charge‐Neutral [Mo24O52(OMe)28] Cages. Issue 53 (1st August 2022) - Wang, Yingyue; Ma, Xinyi; Li, Guoao; Li, Huafeng; Wang, Quanzhong; Chen, Wenjing; Ma, Pengtao; Li, Shuhua; Niu, Jingyang; Wang, Jingping
Abstract: We synthesized a high‐nuclear isopolymolybdate cluster (n‐Bu4 N)6 H2 [Mo24 O48 (OMe)32 Mo24 O52 (OMe)28 2 ] ⋅ 25H2 O ⋅ 6CH3 CN (1) by using [Mo6 O19 ] 2− as the base precursor. Crystallographic characterization shows the cluster is composed of an anionic [Mo24 O48 (OMe)32 ] 8− cage and two charge‐neutral [Mo24 O52 (OMe)28 ] cages. Supported by the electrospray ionization mass spectrometry study, the polyoxoanion structural unit [Mo24 O48 (CH3 O)27 ] 3− demonstrates strong stability in acetonitrile solution. Moreover, 1 exhibits good proton conductivity of 1.79×10 −3 S cm −1 at 358 K and 98 % relative humidity. Abstract : A new 24‐nuclearity polymolybdate (n‐Bu4 N)6 H2 [Mo24 O48 (OMe)32 Mo24 O52 (OMe)28 2 ] ⋅ 25H2 O ⋅ 6CH3 CN (1 ), which consists of an anion [Mo24 O48 (OMe)32 ] 8− cage and two charge‐neutral [Mo24 O52 (OMe)28 ] cages is presented. Compound 1 exhibits good proton conductivity of 1.79×10 −3 S cm −1 at 358 K and 98 % relative humidity.